Stakeholders' aversion to inequality and bank lending to minorities - Matteo Crosignani; Hanh Le (Federal Reserve Bank of New York, 2023)
We find that banks differ in their propensity to lend to minorities based on their stakeholders' aversion to inequality. Using mortgage application data collected under the Home Mortgage Disclosure Act, we document a large and persistent cross-sectional variation in banks' propensity to lend to minorities. Inequality-averse banks have a higher propensity to lend to borrowers in high-minority areas and, within census tracts, to non-white borrowers compared to other banks. This higher propensity (i) is not explained by selection of applicants, (ii) allows these banks to retain and attract their inequality-averse stakeholders, and (iii) does not predict worse ex-post loan performance.
Keywords: G21; J15; E51; 330; inequality aversion; mortgage lending; minority borrowers; racial discrimination